A novel method for the synthesis of solvent-free Mg(B3H8)2. Issue 9 (14th December 2015) - Huang, Jianmei; Yan, Yigang; Remhof, Arndt; Zhang, Yucheng; Rentsch, Daniel; Au, Yuen S.; de Jongh, Petra E.; Cuevas, Fermin; Ouyang, Liuzhang; Zhu, Min; Züttel, Andreas
Abstract : A novel and solvent-free method for the synthesis of Mg(B3 H8 )2 by a gas–solid reaction between B2 H6 and Mg2 NiH4 is presented. Abstract : This communication presents a novel and solvent-free method to synthesise Mg(B3 H8 )2 via the gas–solid reaction between B2 H6 and Mg2 NiH4, which overcomes the limitations of wet chemical methods requiring solvent removal.